DEVELOPING STUDENTS' SPEAKING ABILITY THROUGH THE PROVISIONS OF ACTIVITIES IN ACCORDANCE WITH THEIR LEARNING STYLES - Razak, Yunita Abdul (2009)
his present study focuses on the provisions of activities according to the students' learning styles to develop their speaking ability. This study is designed to answer the following research questions: (1) do the provisions of activities according to students' learning styles develop their speaking ability? (2) which activities do help more each group of learning styles (visual,auditory and kinesthetic) to develop their speaking ability? This study was pre experimental research, applying One-Group Pretest - Posttest design. The objectives of this study were: (1) to investigate whether providing speaking activities based on the students' learning styles can develop the students' speaking ability. (2) to find out which activities help more each group of learning styles to develop their speaking ability. Data were collected over one and a half month period research through students' speaking scores in pretest and posttest. The target population of this study was 137 second year students of Junior High School. The study involved 38 students selected from the population through the purposive sampling. The data were analyzed using Analysis of Variance (ANOVA). This research was conducted in three sessions of applying three different treatments. Session #1 was applying picture describing and narrating conducted in two times treatment. Session #2 was applying discussion activity conducted in two times treatment. Session #3 was applying role play activity conducted in two times treatment. The results showed that from six times treatments given to the students in three sessions, succeeded to improve students' speaking ability. ANOVA results of each session listed that F obs for session #1 was 7.020, session #2 was 4.07, and session #3 was 4.575. It indicated that there was a significant difference among the groups when the activities were applied. It was listed that in session #1, visual learners got the highest scores among the groups meaning that Picture Describing and Narrating helped more visual learners to develop their speaking ability, in session #2, auditory learners got the highest scores among the groups indicating that Discussion activity helped more auditory learners to develop their speaking ability, and in session #3, kinesthetic learners got the highest scores among the groups showing that role play activity helped more kinesthetic learners to develop their speaking ability.